2016
DOI: 10.1016/j.annepidem.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in cervical cancer survival among Asian-American women

Abstract: Purpose We compared overall survival and influencing factors between Asian American women as a whole and by subgroup with white women with cervical cancer. Methods Cervical cancer data were from the Surveillance, Epidemiology, and End Results registry; socioeconomic information was from the Area Health Resource File. We used standard tests to compare characteristics between groups; the Kaplan-Meier method with log-rank test to assess overall survival and compare it between groups; and Cox proportional hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
4
17
0
Order By: Relevance
“…A recent nationwide analysis in the UK showed that women aged 65 years or older accounted for 20% of incident cases and half of all cervical cancer-related deaths [28,29,30]. Similar findings were reported in the USA [31].…”
Section: Agesupporting
confidence: 72%
“…A recent nationwide analysis in the UK showed that women aged 65 years or older accounted for 20% of incident cases and half of all cervical cancer-related deaths [28,29,30]. Similar findings were reported in the USA [31].…”
Section: Agesupporting
confidence: 72%
“…Race was defined as Black or non-Black race, given previous data suggesting similar survival rates for Hispanic and Asian patients compared with White patients. 13,14 Optimal treatment was defined as receipt of surgery or radiation therapy (RT), including brachytherapy for patients with stage IA-IB1 or IIA1 disease. For stage IB2, IIA2, or IIB-IVA or nodepositive disease, optimal treatment was defined as receipt of RT and chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…[ 7 ] Despite these efforts, cervical cancer is still the leading cause of death among many Asian Americans, including KAIs. [ 8 ] Immigrants are generally the most vulnerable population in the context of health-care access and public health services. [ 9 ] Many KAIs are unable to take advantage of medical privileges due to cultural and linguistic barriers, limited access to high-quality health services, and providers' limited knowledge of KAI patients and their culture.…”
Section: Introductionmentioning
confidence: 99%